Pengembangan Buku Berbasis Kontekstual untuk Meningkatkan Karakter Pelajar Pancasila - Kurnia, Ira Restu (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
This research is a type of development research (Research and Development/RnD) that uses the Borg and Gall development model. The purpose of this research is to produce a product in the form of contextual-based book learning media in improving the character of Pancasila students. The research subjects were 32 students of class V at SDN Cililitan 02 Jakarta. Based on research conducted, data obtained in the form of a feasibility percentage by material experts showed data of 85% with a very feasible category. Furthermore, the language feasibility test shows a percentage of 93% with a very decent category. Then the media expert due diligence showed a percentage of 89% in the very feasible category. Besides that, there was also a large gain in the aspect of the media effectiveness test, which was 94% in the very effective category. The same thing is shown by the presentation data from the due diligence by small group users of 89% with the very feasible category. then the large group test obtained a percentage of 93% with a very feasible category. based on these data, the contextual-based book media is proven to be able to improve the character of Pancasila students in students.